Association between Frailty and Mortality, Falls, and Hospitalization among Patients with Hypertension: A Systematic Review and Meta-Analysis - Hu, Kaiyan (Biomed Res Int, 2021)
OBJECTIVE: Chronological age alone does not adequately reflect the difference in health status of a patient with hypertension. Frailty is closely associated with biological age, and its assessment is clinically useful in addressing the heterogeneity of health status. The purpose of our study is to comprehensively examine the predictive value of frailty for negative health outcomes in hypertensive patients through a systematic review and meta-analysis. METHODS: Multiple English and Chinese databases were searched from inception to 04.11.2020. All cross-sectional and longitudinal studies that examined the association between frailty and relevant clinical outcomes among hypertensive patients were included. The NOS was used to assess the risk of bias of studies included in the analysis. Hazard ratios (HRs), odds ratios (ORs), and 95% confidence intervals (CIs) were pooled for outcomes associated with frailty. RESULTS: Six longitudinal studies and one cross-sectional study involving 17403 patients with hypertension were included in the meta-analysis. The risk of bias of all included studies was rated as low or moderate. The pooled HR of frailty related to mortality was 2.45 (95% CI: 2.08-2.88). The pooled HR of prefrailty and frailty-related injurious falls was 1.07 (95% CI: 0.83-1.37) and 1.89 (95% CI: 1.56-2.27), respectively. The pooled HR of prefrailty and frailty-related hospitalization was 1.54 (95% CI: 1.38-1.71) and 1.94 (95% CI: 1.17-3.24), respectively. CONCLUSIONS: This systematic review suggests that frailty was a strong predictor of mortality, hospitalization, and injurious falls among patients with hypertension. Our findings indicate that assessment of frailty in patients with hypertension to guide their management may be necessary in clinical setting. However, our finding was based on very limited amount studies; thus, future studies are required to further validate the role of frailty in prediction of negative health outcomes in hypertensive patients as well as pay more attention to the following knowledge gaps: (1) the association between frailty and hypertension-related outcomes, (2) the significance of the association between different frailty models and relevant clinical outcomes, and (3) the predictive value of prefrailty for the negative health outcomes in people with hypertension.